Efektifitas Metode Pembelajaran Make-A-Match Dalam Meningkatkan Hasil Belajar IPA Materi Transformasi Energi Pada Siswa Kelas IV SDN Wiroborang 1 - Anjarwati, Ani; Rohman, Adella Pramesti Ekaditya; Karimah, Inayatul; Putra, M Triya Reza (CV. ITTC INDONESIA, 2022)
The research was conducted to determine the impact of student learning outcomes with science learning material on energy transformation which was applied using the make-a-match type of learning method. In addition, showing interactive videos and PowerPoint also supports learning activities that can help students in the process of understanding each material that will be provided. The make-a-match method is very efficiently applied to teaching and learning activities in elementary schools. In addition to learning, students can also play games to match question cards. The make a match type of cooperative learning method aims to generate mutual respect between students, form an attitude of responsibility in students, increase self-confidence in solving a problem, find the best solution and demand active and creative students in every teaching and learning activity. This study used a class action method by collecting data through a questionnaire in the form of questions regarding the energy transformation material. Techniques for collecting data in our study were observation, written tests and documentation. The design of this research consists of four main activities that have been determined, namely: planning such as making lesson plans, implementing the intended class action, observing the results of student scores, and finally reflecting. In this realm researchers must focus, because it will have an impact on student learning outcomes and can apply it in everyday life.